Who Are “the Parties” for Purposes of VCLT Article 31(3)(c)? A Case Study in WTO Pragmatism - Cook, Graham (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
Article 31(3)(c) of the Vienna Convention on the Law of Treaties (VCLT) provides that a treaty interpreter must take into account “any relevant rules of international law applicable in the relations between the parties.” The meaning of “the parties,” and more specifically whether there is a precondition that all parties to the treaty being interpreted must also be parties to the other treaty for the latter to qualify under Article 31(3)(c), has been the subject of much academic debate. The question does not necessarily have an obvious answer, and has been seen as being a consequential issue in the WTO context because of a perception among some commentators that: (a) taking non-WTO treaties into account could be a decisive consideration in the interpretation of certain WTO provisions; and (ii) under a strict reading of “the parties”, very few non-WTO treaties would meet the requisite threshold. This article explains how WTO adjudicators have pragmatically bypassed and largely defused this contentious issue by referring to non-WTO treaties effectively as “supplementary means” of interpretation, or, more commonly, as evidence of facts—purposes that arguably could fall outside the purview of Article 31(3)(c).